Effect of management and seed rate on the performance of wheat varieties with varying seed sizes (Bangladesh Journal of Agricultural Research, 2009)
An experiment was conducted with three wheat varieties of varying seed sizes at five seed rates in medium and high management at Wheat Research Centre, Dinajpur during 2004-05 Rabi season to determine the appropriate seed rates for the varieties under different management practices. On an average, high management increased grain yield by 18.4%, but the benefit-cost ratio (BCR) was higher in medium management. Higher grain yield was obtained from varieties Shatabdi (medium sized seed) and Prodip (large sized seed) compared to Sufi (small sized seed) in high management, whereas in medium management, all the varieties produced similar grain yield. Considering yield performance and BCR analysis, the seed rates of Sufi and Shatabdi might be 100 and 120 kg/ha, respectively, for both the managements. Seed rates of Prodip might be 120 and 140 kg/ha for medium and high management, respectively. Key Words: Management, seed rate, seed size, variety. DOI: 10.3329/bjar.v34i3.3975 Bangladesh J. Agril. Res. 34(3) : 481-492, September 2009